1997
DOI: 10.1063/1.473757
|View full text |Cite
|
Sign up to set email alerts
|

The ground state (1A1) and the lowest triplet state (3B1) of the phenyl cation C6H5+ revisited

Abstract: The electronic states of 1,2,3-triazole studied by vacuum ultraviolet photoabsorption and ultraviolet photoelectron spectroscopy, and a comparison with ab initio configuration interaction methods J. Chem. Phys. 134, 084309 (2011); 10.1063/1.3549812Structure and properties of the low-lying electronic states of Ce C 2 and Ce C 2 +

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 36 publications
(29 reference statements)
0
21
0
Order By: Relevance
“…The ionization of phenyl radical may involve the removal of the unpaired electron from the localized orbital of the bare C atom or an electron from the orbital of the six-carbon ring structure, resulting in the singlet C 6 H 5 + ͑ 1 A 1 ͒ and triplet C 6 H 5 + ͑ 3 B 1 ͒ cationic states, respectively. Previous theoretical studies 51,52 indicate that the triplet phenyl cation C 6 H 5 + ͑ 3 B 1 ͒ is higher in energy than the singlet phenyl cation C 6 H 5 + ͑ 1 A 1 ͒ by Ϸ0.8− 0.9 eV. The structure of the C 6 H 5 + ͑ 3 B 1 ͒ cation is expected to be similar to that of phenyl radical.…”
Section: B Ionization Energy Of C 6 H 5 and Heats Of Formation Of C mentioning
confidence: 84%
“…The ionization of phenyl radical may involve the removal of the unpaired electron from the localized orbital of the bare C atom or an electron from the orbital of the six-carbon ring structure, resulting in the singlet C 6 H 5 + ͑ 1 A 1 ͒ and triplet C 6 H 5 + ͑ 3 B 1 ͒ cationic states, respectively. Previous theoretical studies 51,52 indicate that the triplet phenyl cation C 6 H 5 + ͑ 3 B 1 ͒ is higher in energy than the singlet phenyl cation C 6 H 5 + ͑ 1 A 1 ͒ by Ϸ0.8− 0.9 eV. The structure of the C 6 H 5 + ͑ 3 B 1 ͒ cation is expected to be similar to that of phenyl radical.…”
Section: B Ionization Energy Of C 6 H 5 and Heats Of Formation Of C mentioning
confidence: 84%
“…Several of its electronic properties have been measured, including its ultraviolet absorption spectrum, 13,14 ionization potential, 15,16 photoionization cross section, 17 and electron affinity. 18 The electronic states and vibronic spectra of the phenyl radical have also been calculated.…”
Section: Introductionmentioning
confidence: 99%
“…Transfer of an electron from the π‐system to the empty σ‐orbital6 restores the sp 2 hybridization at the cost of forming a triplet ( 3 B 1 ) electronic state and sacrificing the aromaticity of the system 4. By now, a singlet ( 1 A 1 ) ground state about 77 kJ mol −1 lower in energy than the triplet has been firmly established 7…”
Section: Methodsmentioning
confidence: 94%
“…Values for the singlet–triplet energy gap obtained using other computational methods indeed show significant scatter, favoring the triplet state (PM3,17 CISD, ROHF,18 HF19) or the singlet state (MP2,19 CCSD(T)15) by substantial amounts. This result suggests that a multireference approach as has been applied to the phenyl7 and vinyl13 cations may be required in this case as well. On the other hand, the study on substituted vinyl cations found good agreement between DFT and CASPT2 values for the singlet–triplet gap,13 encouraging the use of low‐cost DFT methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation